Functional and Semantic Identification of Occasionalisms in the Language of Ukrainian Periodicals (Linguostylistic Studies, 2016)
The article analyzes the functioning of occasionalisms in the language of Ukrainian periodicals. In the focus of attention is the role of occasionalisms in the creation of judgements and emotionality in the newspaper texts, their influence on the formation of value judgments among readers. The author has made an attempt to classify occasionalisms according to their field of application. The overall analysis indicates that periodicals are one of the most productive sources of coining new words and new meanings of words, to nominate the new and up-to-date notions. This is due to the fact that the media inform daily about the news in various fields of life, science, politics, production and reflect the reality in its entirety, in the dialectical development, and provide inexhaustible possibilities to supplement the vocabulary of the Ukrainian language. Occasioalisms are of specific semantic nature and are characterized by peculiar functional and stylistic designation. Occasionalisms are to some extent a violation of the grammatical, word-building and semantic rules, but this violation is not due to ignorance of the literary norms or the inability to use them, but is a deliberate process. Key words: occasionalisms, periodicals, author's neologisms, negative evaluation. References